Diarrhoea and Constipation in Geriatric Practice. - Ratnaike, Ranjit N. (Cambridge University Press, 2003)
This textbook provides a practical and comprehensive account of the management of diarrhoea and constipation in the elderly. These common disorders are not only a burden in themselves but are often manifestations of a more serious underlying illness; thus, effective diagnosis and treatment are essential to improve quality of life. The chapters include updates on pathogenesis, diagnosis and treatment, and highlight the vulnerability of the elderly to diarrhea and its complications.